2022
DOI: 10.3389/fimmu.2022.937307
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib: A Novel Antiangiogenic Drug in Monotherapy or Combination Immunotherapy for Digestive System Malignancies

Abstract: Digestive system malignancies are one of the primary causes of cancer-related death. Meanwhile, angiogenesis has been proved to play an important role in the process of cancer neovascularization. Apatinib, a novel targeted antiangiogenic molecule, could generate highly selective competition in the vascular endothelial growth factor receptor-2, involved in tumor progression and metastasis. It has been implied as a promising cancer treatment agent that can prevent tumor cell proliferation meanwhile inhibit tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…Our study showed that the three experimental groups promoted the in ltration of CD4 + and CD8 + T cells into the TME with varying degree, and the in ltration of CD4 + and CD8 + T cells in the combination therapy group was greater than that in the other groups. Similar results have been reported in digestive system malignancies [32]. CD8 + T cells interrupt angiogenesis by secreting IFN-γ [25].…”
Section: Discussionsupporting
confidence: 85%
“…Our study showed that the three experimental groups promoted the in ltration of CD4 + and CD8 + T cells into the TME with varying degree, and the in ltration of CD4 + and CD8 + T cells in the combination therapy group was greater than that in the other groups. Similar results have been reported in digestive system malignancies [32]. CD8 + T cells interrupt angiogenesis by secreting IFN-γ [25].…”
Section: Discussionsupporting
confidence: 85%
“…[28] In previous studies, apatinib was shown to have an effect on human patients who had received chemotherapy for thyroid cancer and other advanced cancers, such as gastric cancer (6.5 vs 4.7 months, P = .0149), liver cancer, colorectal cancer, and breast cancer. [29][30][31][32] It can effectively exert antitumor effects. Previous clinical studies have shown that apatinib is a viable treatment option for advanced thyroid cancer with significant efficacy in ORR, PFS, and OS, and a good safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, apatinib was regarded as an anti-angiogenesis inhibitor against VEGFR-2, similar to drugs of a similar type, namely, sorafenib, sunitinib, and cabozantinib ( 31 ). Considering the limited efficiency of other anti-angiogenesis inhibitors, such as cediranib ( 32 ) in advanced NSCLC, it is rather possible that mechanism of apatinib may be different ( 33 ). Apatinib may also possess other targets, such as RET, FlT3, and so on ( 34 ).…”
Section: Discussionmentioning
confidence: 99%